THE ROLE OF EDMODO VIRTUAL CLASS TOWARD THE STUDENTS’ WRITING ABILITY IN REMOTE ISLAND - Iksan, Iksan (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2018)
The objectives of this research were to find out (1) whether or not the use of Edmodo virtual class increases the motivation of the students of SMA Negeri 24 Karanrang island Pangkep in writing English and (2) the extent to which Edmodo virtual class increases students’ writing achievement. The population was all the students of SMA Negeri 24 Karanrang island at Pangkep regency in academic year 2018/2019. The students in this remote area were consisted of 30 students merely. Involving two classes (class X and class XI), selected by using total sampling technique, this research employed quasi experimental design (15 students as experimental class that was taught by using Edmodo virtual class and 15 students as control class that was taught by lecturing way). The data then collected through questionnaire (of writing motivation) and writing test, then analyzed through descriptive statistics and inferential statistic (SPSS) program version 22. The result gained from the data analysis showed that (1) the use of Edmodo virtual class in writing motivation was significantly different from the existing way. (2) The use of Edmodo virtual class in writing achievement increases the students’ writing achievement